Occlusion training increases muscular strength in division IA football players - Yamanaka, T.; Farley, R. S.; Caputo, J. L. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to investigate the effectiveness of 4 weeks of low-intensity resistance training with blood-flow occlusion on upper and lower body muscular hypertrophy and muscular strength in National Collegiate Athletic Association Division IA football players. There were 32 subjects (average age 19.2 ± 1.8 years) who were randomized to an occlusion group or control group. The athletes performed 4 sets of bench press and squat in the following manner with or without occlusion: 30 repetitions of 20% predetermined 1 repetition maximum (1RM), followed by 3 sets of 20 repetitions at 20% 1RM. Each set was separated by 45 seconds. The training duration was 3 times per week, after the completion of regular off-season strength training. Data collected included health history, resting blood pressure, pretraining and posttraining bench press and squat 1RM, upper and lower chest girths, upper and lower arm girths, thigh girth, height, and body mass. The increases in bench press and squat 1RM (7.0 and 8.0%, respectively), upper and lower chest girths (3 and 3%, respectively), and left upper arm girth were significantly greater in the experiment group (p < 0.05). Occlusion training could provide additional benefits to traditional strength training to improve muscular hypertrophy and muscular strength in collegiate athletes.